PEMANFAATAN MEDIA GAMBAR ACAK (PICTURE AND PICTURE) UNTUK MENINGKATKAN PRESTASI BELAJAR BAHASA INDONESIA - Subiah Subiah (LPPM UNISDA, 2018)
This study aims to determine the implementation of learning with random image media (picture and picture) and improving learning achievement of Indonesian subjects aspects of writing class III SD Katemas II Elementary School, Kembangbahu Subdistrict, Lamongan Regency in the academic year 2016/2017. The subjects of this study were all third grade students of SD Negeri Katemas II, which amounted to 6 people. This study belongs to a classroom action research consisting of several cycles with each cycle consisting of planning, action, observation, and reflection. Instruments used in the form of Learning Plans (RP), Student Activity Sheets (LKS), and grade assessment. The result of the research showed that the improvement of student learning outcomes from cycle I was 59.17 to 84.17 in cycle II. Thus, it can be concluded that there is the influence of the use of random image media (Picture and Picture) to improve students' ability to write simple essay based on drawing series.